Recreational sport as antidote for managing anti-social behaviour among the youths for sustainable national security in nigeria (2013)
Youth participation in sport creates enduring legacy for good will and opportunity for sound human relations. Sport is a social agent and unifying factors that brings people of different ages, religion and political background together. It senses as a great melting pot for peoples, races and cultures. In other to prevent deviant, hatred and other anti social behaviour like sex harassment, stealing, truancy vandalize oil pipe and electric cable and emulate good character that is inform with societal norms, youth should be encouraged to participate in sporting activities that ./ill promote cohesion and enhance proper behaviours for better human relations. The paper, -.therefore examined various anti social behaviours exhibited by Nigerian youths, the causes and 'ow incredible behaviours can be managed for sustainable national security